Hubungan Peran Keluarga Dan Motivasi Pasien Stroke Dengan Kepatuhan Kunjungan Di Poliklinik Syaraf RSUP DR. M. Djamil Padang - Reni Trevia; Firda Damba Wahyuni (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2022)
Stroke is a clinical syndrome that early onset of sudden, progressive, fast form of vocal or global neurological deficit lasting 24 hours or directly cause death. The prevalence of stroke in Indonesia is increasing every year, by 7.0 to 12.1 per 1000 population from 2013-2014. Datain Neurosurgery Clinic DR. M. Djamil Padang, the number of stroke patients in the Neurology Clinic in the last 3 month last from May until July 2022, there were 152 people.. The purpose of this study was to determine the role of Family Relations and Motivation with compliance visits in Neurosurgery Clinic DR. M. Djamil Padang This types of research is descriptive analytic with cross sectional studied design. This research has been conducted on the space clinical Neural DR. M. Djamil Padang in November 2022. Total population of 152 people, the total sample of 60 respondents, data retrieval time from September until November 2022 with Accidental Sampling technique. Data is processed in a computerized and analyzed by univariate from of frequency distribution and bivariate analysis using chi-square test (p-value ≤ 0,05). The result showed more than half of patients had a compliance visited (53,3%), the role of the family (71,7%), motivation (56,7%). The existence of a significant association between family roles (p=0,002), and the relationship of motivations with compliance visits (p=0,001). Suggested to the departement of health workes DR. M. Djamil Padang to provide health information to patients who visited the clinic and gived direction to the patients family to get involved in assisting patients in treatment